”Strange Frankness” : The Descriptive Use of Allusions in Fanny Kemble’s 1835 American Journal - Rennes, Linda (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis examines the descriptive use of allusions in Fanny Kemble’s Journal by Frances Anne Butler (1835). Allusions are cultural references that not only enrich the text but often go beyond the mere words used, implying a deeper, hidden meaning. They always mirror the author’s persona, reflecting their thoughts, opinions, and feelings. In this thesis, I will study how Kemble has used allusions as a means of description as well as analyse the hidden meanings behind her allusions. This thesis studies the first volume of Kemble’s journal, which consists of 84 journal entries. It is her first published autobiographical writing, the journal she kept as a young actress on her theatre tour in America. The reception of the journal was controversial, as the contemporary reviews criticised both her writing style and persona. The critical reception can partly be seen as a reflection of the nineteenth-century mind-set, for Kemble’s modern and feminist voice was clearly ahead of her time. Kemble’s distinct writing style is characterised by its frequent use of cultural allusions. However, this noted feature in her writing has not been studied before this thesis. Based on observations made in contemporary reviews of the journal, the descriptive allusions have been divided into three categories: allusions about others, allusions about herself, and allusions about nature. This thesis is based on a multifaceted analysis of allusions, in which the form, style, theme, and function of each allusion is examined. The theoretical framework combines allusion theories from Leppihalme (1997), Kirillov (2003), Ruokonen (2010), and Lennon (2004). My analysis sheds light on the complexity of Kemble’s allusions as well as the nuanced differences present as the subject of description varies. Based on the findings of my analysis, I present two new functions of allusions that are significant in Kemble’s journal, but have not been taken into account in the theories on which I based my analysis. These functions are: to praise and to exaggerate. The findings of my thesis suggest that there is an academic need for a more detailed categorization of the functions of allusions.